Implementation and Issues of Land Procurement for Customary Rights in the Development of Plasma Oil Palm Plantations in Kampung Lama Pakis Pakobuk - Nabima, Muhammad; Djaja, Benny (Trunojoyo Madura University, 2025)
The absence of a legal mechanism regarding the release of customary land for private interests has weakened legal protection for the rights of indigenous peoples. Furthermore, the land acquisition process is often carried out without implementing the principle of Free, Prior and Informed Consent (FPIC). This research is normative legal research with a qualitative approach, supported by a case study of the High Court Decision Number 175/PDT/2022/PT PRB. Data was obtained through literature review, legal analysis of related laws and regulations, and documentation of court decisions related to customary land disputes. The results of the study show that the implementation of land acquisition in Kampung Lama Pakis Pakobuk does not reflect agrarian justice. The imbalance in bargaining position between corporations and indigenous peoples, weak supervision of local governments, and minimal formal legal recognition of customary areas are the main problems identified. Therefore, it is necessary to reconstruct agrarian law that operationally accommodates customary rights in the national legal system. The government also needs to form a special institution to monitor and mediate land acquisition conflicts based on community participation, so that future customary land acquisition can be carried out fairly and sustainably.